IMPLEMENTASI AKUNTANSI DAN MANAJEMEN BAGI PENGUSAHA RENGGINING DESA KOLEANG, KECAMATAN JASINGA, BOGOR - Mulyaning Wulan; Ummu Salma Al Azizah (SYUKUR (Jurnal Inovasi Sosial dan Pengabdian Masyarakat), 2019)
Koleang Village is located in jasinga District, West Java. With a population of approximately 5,000 residents, Koleang is the most populated village of its population compared to other villages in the vicinity such as Karundang, Cicanggong, Silongong, Sampalan Kadu, Cisarua and other villages. Traditional food makers, namely Renggining and Dapros, snack-shaped foods are one of the drivers of the economy for most of the Koleang people. However, it is very regrettable that the lack of understanding of the people about the importance of good financial management has made the efforts that they have made for livelihoods for years difficult to develop. PKM Team from Muhammadiyah University Prof., DR Hamka, is also a lecturer who has a dedication to carry out the Chess Darma College. It is expected that through the training held can increase accounting capabilities through training in financial report making. In addition, business operators are expected to have the ability to manage their business, especially in innovation and marketing. Keywords: Micro Business, Internet-based Marketing, Business Management, Community Service (PKM)